SUSTAINABILITY OF EXCHANGE RATES AND CRUDE OIL PRICES CONNECTION WITH COVID-19: AN INVESTIGATION FOR BRICS - PARUL BHATIA (Analele Universităţii Constantin Brâncuşi din Târgu Jiu : Seria Economie, 2021)
The study has investigated relationship between crude oil prices and exchange rates of BRICS region from 1999-2020. A comparison has been drawn in normal and COVID-19 period for analysing the cause-and-effect bivariate relationship in two different periods. The COVID-19 crisis period has been analysed along with normal period to explore differentiation between the two periods. OLS and DCC-GARCH model has been employed to empirically test the causal linkages from crude oil prices to exchange rates of BRICS group of countries. There existed a long run volatility from crude oil prices to exchange rates of BRICS countries both in normal and COVID times. The relationship may have been impacted temporarily during pandemic and crisis period. However, the causal linkage has been strong and results in both periods have been found in line with the existing literature baring minor exceptions. The policy makers and global investors may benefit from the results of the present study.